Navigating EFL Classrooms: A Functional Analysis of Code-Mixing and Code-Switching as Instructional Strategies - Ayang Winda Sri Widianingsih; Tinanthy Rosse Santosa Santosa (Jurnal Dimamu, 2026)
This research investigates the phenomenon of code-mixing and code-switching used by a teacher and fourth-semester students in an English as a Foreign Language (EFL) speaking class at a university in Bandung. The study is grounded in the fact that while learning a new language influences communication choices, excessive reliance on code-switching (CS) and code-mixing (CM) may hinder the mastery of English grammatical rules. This study aims to identify the specific types of CS and CM that occur during classroom interactions. Using a descriptive qualitative case study design, data were collected through online observations via Zoom meetings and audio recordings, which were then transcribed and analyzed using Poplack’s (1980) and Muysken’s (2004) frameworks. The results reveal that only specific types of linguistic shifts occurred: intra-sentential and inter-sentential switching were the primary forms of CS used by the teacher to ensure student understanding. Meanwhile, CM was manifested through insertion—such as adding Indonesian affixes to English base words—and alternation. The findings and discussion highlight that students frequently reverted to Indonesian or their mother tongue during group discussions due to vocabulary limitations and a lack of direct teacher monitoring. The study concludes that while these phenomena facilitate material comprehension, teachers should implement strategic rules to limit dependency on non-English codes to optimize students' speaking proficiency.